MULTIOMICS TECHNOLOGIES IN THE STUDY OF THE PATHOGENESIS OF BRAIN ARTERIOVENOUS MALFORMATIONS - Zhamshitova, D.A.; Zholdybayeva, E.V. (Eurasian Journal of Applied Biotechnology, 2025)
Brain arteriovenous malformations (bAVMs) are abnormal vascular structures in which arteries directly connect to veins, bypassing the capillary network. Studying the pathogenesis of bAVMs is important for understanding the mechanisms of their occurrence and development, allowing the development of more effective diagnosis, treatment, and prevention methods. This review aims to collect and analyze data about genes, proteins, and metabolites that affect the pathogenesis of brain AVMs obtained using multi-omics technologies. The use of whole-exome sequencing, RNA-sequencing, TMT-MS, iTRAQ, UHPLC-MS allowed us to identify key genetic mutations, signaling pathways and mechanisms associated with the development of bAVMs. They include the KRAS gene in endothelial cells and the MAPK, Wnt and TGF-β pathways. The discovery of differentially expressed proteins and metabolites such as hydroxyproline, dihydrojasmonic acid, L-2-amino-4-methylenepentanedioic acid, piperettine, 20-hydroxy-PGF2a, 2,2,4,4-tetramethyl-6-(1-oxobutyl)-1,3,5-cyclohexanetrione, DL-tryptophan, 9-oxoODE, alpha-linolenic acid also offers new biomarkers for diagnosis and treatment. The data obtained through multi-omics approaches are critical for developing personalized treatment strategies and improving clinical management, with the ultimate goal of reducing morbidity and mortality associated with brain AVMs.